2014
DOI: 10.1177/0002716214525571
|View full text |Cite
|
Sign up to set email alerts
|

New Partners, More Kids

Abstract: Declining rates of marriage and overall increases in union instability, combined with high levels of unintended and nonmarital fertility, create the possibility for parents to have children with more than one partner, called multiple-partner fertility, or MPF. The unique characteristics of families with MPF present data and other logistical challenges to researchers studying the phenomenon. Drawing from recent studies and updated data, I present new estimates of MPF that show that about 13 percent of men aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 69 publications
0
41
1
1
Order By: Relevance
“…Today, just 40% are expected to be formalized through marriage (Lamidi, Manning, & Brown, 2015). The rising instability of cohabiting unions sets the stage for additional family transitions; specifically, it presents opportunities for repartnering and multiple-partner fertility, exposing children to still more family transitions (Cherlin, 2009; Guzzo, 2014a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, just 40% are expected to be formalized through marriage (Lamidi, Manning, & Brown, 2015). The rising instability of cohabiting unions sets the stage for additional family transitions; specifically, it presents opportunities for repartnering and multiple-partner fertility, exposing children to still more family transitions (Cherlin, 2009; Guzzo, 2014a). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the rise in unmarried births, the continued growth in cohabitation and serial cohabitation, as well as the decreasing tendency for cohabitation to culminate in marriage, point to more family transitions for children (Cohen & Manning, 2010; Guzzo, 2014a, 2014b; Lichter, Turner, & Sassler, 2010). Even children in married families may experience less stability today than in the past given new evidence that divorce has been climbing during the past few decades (Kennedy & Ruggles, 2014).…”
mentioning
confidence: 99%
“…In another study, among mothers who were not married at the time of their first birth, 37 % had a child with another partner by the time their first child reached age 10 (Cancian et al 2011). Further, some evidence suggests that the rate of MPF has increased over time (Guzzo 2014; Monte 2011b), although it may have begun to level off recently (Cancian et al 2013). Because MPF may be not only a reflection of unstable couple relations but also a potential mechanism through which family relationships are weakened and family resources are diminished, MPF has become an increasingly important subject of research for those interested in family well-being (Berger et al 2012; Carlson and Furstenberg 2006; Edin and Kefalas 2005; Guzzo 2014; McLanahan 2009; Monte 2011b; Tach et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has found that MPF is associated with couples’ socioeconomic and demographic characteristics, relationship status, and individual attitudes (Cancian et al 2011; Carlson and Furstenberg 2006; Classens 2007; Curtis and Waldfogel 2009; Kim et al 2015; Guzzo 2014; Guzzo and Furstenberg 2007; Kotila and Kamp Dush 2012; Manlove et al 2008; Meyer et al 2005; Monte 2011b); however, little is known about the ways fathers’ imprisonment contributes to MPF. As imprisonment rates in the United States have risen to be the highest in the industrialized world and are disproportionately high for disadvantaged individuals (Carson 2014; Maguire and Pastore 2007; Walmsley 2009; Western 2006; Western and Pettit 2005), economically vulnerable children face a high and increasing risk of paternal imprisonment (Sykes and Pettit 2014; Wildeman 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation